2011
DOI: 10.1785/0120100153
|View full text |Cite
|
Sign up to set email alerts
|

Faster Short-Distance Earthquake Early Warning Using Continued Monitoring of Filtered Vertical Displacement: A Case Study for the 2010 Jiasian, Taiwan, Earthquake

Abstract: We collected the strong-motion accelerograms from the 2010 Jiasian earthquake (M 6:4) that struck southern Taiwan recorded by the Taiwan Strong-Motion Instrumentation Program (TSMIP) stations to perform an off-line test for our proposed short-distance earthquake early-warning (EEW) approach. The 2010 Jiasian earthquake demonstrates the vital need for the short-distance EEW. The tested short-distance EEW method is a threshold-based approach relying on the amplitude of the filtered vertical displacement. Our res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…The signal resolution is 16 bits with a measurement range from -2 to +2 g. The software algorithm enables the device to capture the initial P-waves and estimate parameters like peak amplitude of displacement (Pd) as it is triggered. When the up-coming seismic waves estimation exceeds the configured thresholds, Pd larger than 3.5 cm or PGA larger than 80 gal, the device starts sending alarms for onsite EEW purposes (Kanamori 2005;Kanamori 2005a, 2005b;Wu et al 2011Wu et al , 2013a.…”
Section: Low Cost Seismic Networkmentioning
confidence: 99%
“…The signal resolution is 16 bits with a measurement range from -2 to +2 g. The software algorithm enables the device to capture the initial P-waves and estimate parameters like peak amplitude of displacement (Pd) as it is triggered. When the up-coming seismic waves estimation exceeds the configured thresholds, Pd larger than 3.5 cm or PGA larger than 80 gal, the device starts sending alarms for onsite EEW purposes (Kanamori 2005;Kanamori 2005a, 2005b;Wu et al 2011Wu et al , 2013a.…”
Section: Low Cost Seismic Networkmentioning
confidence: 99%
“…Wu et al (2011) tested a short-distance EEW approach for the 2010 Jiasian earthquake, which is a threshold-based approach using continued monitoring of filtered vertical displacements. They showed that the tested short-distance EEW approach can provide a timely warning for the target sites located less than 50 km away from the epicenter.…”
Section: Earthquake Hazards Potential In Southern Taiwanmentioning
confidence: 99%
“…During strong ground shaking, a crane operating on top of the construction area of the Taipei 101, the tallest building in Taiwan (508 m tall), crashed and dropped to the ground. The 2010 M w 6.3 Jiasian earthquake brought strong ground motions to southern Taiwan, causing an operating Taiwan High Speed Rail train to run off its tracks (Huang et al, 2011;Wu et al, 2011). Given these types of incidents in Taiwan, a reliable and fast EEW system is urgently needed to provide early warnings for the next large earthquake.…”
Section: Introductionmentioning
confidence: 99%